An interrupted time series analysis of the effect of the quality improvement team on the rate of adverse events in the Botswana safe male circumcision program from 2015 to 2019 - Ludo S. Monene; Billy M. Tsima; Keikantse Matlhagela; Mooketsi Molefi (PLoS ONE, 2025)
Background Voluntary medical male circumcision (VMMC) has been shown to reduce heterosexual human immune deficiency virus (HIV) transmission. In 2009, Botswana rolled out its VMMC program to expand existing HIV preventive strategies. However, in 2017, a study recorded an adverse event rate (AER) of 6.7% in Botswana. A quality improvement team was introduced to help reduce AER through standardized training and mentorship by ensuring that the World Health Organization VMMC and the Botswana safe male circumcision program standards are met. We hypothesized that t he introduction of the quality improvement team reduced the trend and magnitude of the moderate and severe AER for the day 7 routine follow-up visit. Methods A quasi-experimental study was conducted using data from monthly district reporting tools. Interrupted time series analysis was used to compare the trend and magnitude of the moderate and severe AERs after circumcision for the day 7 routine follow-up visit in males aged 10 years and older. The comparison was done two years before (April 2015 to March 2017) and two years after (April 2017 to April 2019) the introduction of the quality improvement team. The most common adverse events (AEs) by age category, type, and severity between April 2015 and April 2019 were also reported. Frequencies and percentages were used to summarize the descriptive measures. Where indicated, all measures are reported with 95% confidence interval and statistical significance set at p ≤ 0.05. Results There was an overall downward trajectory of the day 7 moderate and severe AER throughout the study period. Nonetheless, prior to the intervention, the moderate and severe day 7 AER decreased significantly monthly by 0.1% (p = 0.046, 95% CI = −0.195, 0.002). However, after the intervention, the AER insignificantly increased by 0.08% (p = 0.107, 95% CI = −0.018, 0.181). Majority (68.5%) of the AEs occurred in the 10–14 years age category. Most of these AEs were mild (73.8%). Infections were the most common AE (45.1%). Conclusion The effect of the quality improvement intervention on the rate of AEs was minimal. Regular audits and further research on why the quality improvement team was not able to significantly reduce the AER would be beneficial.